Peningkatan proses dan hasil belajar matematika menggunakan model make a match untuk peserta didik kelas III SDN 101/II Muara Bungo - Mozakiyah Dinda Sari; Randi Eka Putra; Nurlev Avana (LPPM STAI Muhammadiyah Probolinggo, 2025)
The primary concern of the study is the poor learning process andoutcomes in mathematics classes for third-grade students at SDN 101/IIMuara Bungo. This initiative aims to improve the mathematics learningprocess and outcomes for third-grade students at SDN 101/II MuaraBungo by utilizing the Make A Match technique. Two meetings are heldduring each of the two cycles of this classroom action study. Each cycleconsists of the following phases: planning, execution, observation, andreflection. In the second semester of the 2025 academic year, this studywas conducted in SDN 101/II Muara Bungo. The learning process, whichincludes observations of student activities, interactions betweenteachers and students, classroom management, and learning materials,is where the study's findings are evident. During cycle 1, educatorobservations received 85.71% in the very good category, and duringcycle 2, they received 97.61% in the very good category. Similarly,during cycle 1, student observations received 66.57% in the fairly goodcategory, and during cycle 2, they received 85.31% in the very goodcategory. According to the study's findings, the percentage of studentswho completed the test and obtained KKTP in the initial conditions was34.37%, or 11 out of 32 students; in cycle I, the percentage of studentswho achieved KKTP was 66.66%, or 18 out of 27 students; and in cycleII, the percentage of students who achieved KKTP was 92.85%, or 26out of 28 students.